Evaluation of Developmental Delay in Infants Who Came in for 6th Month Vaccination in Isfahan City Health Centers - YAGHINI, Omid; DANESH, Farzaneh; MAHMOUDIAN, Touran; BEIGI, Babak; EBRAHIMIAN, Shiva (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Yaghini O, Danesh F, Mahmoudian T, Beigi B. Evaluation of Developmental Delay in Infants Who Came in for 6th Month Vaccination in Isfahan City Health Centers. Iran J Child Neurol 2012;6(2): 29-32. Objective Developmental delay is one of the most common causes of conferring the pediatric neurologist. The main part of neurological growth and development occur in the first two years especially in the first 6 months of life. Metabolic or skeletal diseases are important causes of developmental delay. Early diagnosis of deviance from the normal diagram of development in lower ages is important. Materials & Methods Specific ages and stages questionnaires (ASQ) for 6 months was completed in the health centers for 800 infants conferring for their vaccination in Isfahan and the retest was performed at 24 months of age by ASQ and then these two questionnaires were compared. Results 10.5% of the infants were delayed in at least one domain. At 24 months, 38.4% of them remained delayed; 21.1% in one domain, 9.6% in two domains, 3.8% in four domains and 3.8% in five domains. Of the children who had problem in communication, 20%; in gross motor, 25%; in fine motor, 20%; and in problem solving, 30% remained delayed. In the personal social domain, none of the delayed children at 6 months remained delayed at 24 months. Conclusion ASQ is feasible, inexpensive, easy to use and was appreciated by the parents. It can be used as a screening test for detection of developmental delay in lower ages, but its results must be followed by other standard tests or diagnostic tools. References Lewis R, Palfreg GS. The infant or young child with developmental delay. The New England J Med 1994;330:478-83. Cleary MA, Green A. Developmental Delay: when to suspect and how to investigate for an inborn error of metabolism. Arch Dis Child2005;90(11):1128-32. Schendel DE, Stockbauer JW, Hoffman HJ, Herman AA, Berg CJ, Schrann WF. Relation between very low birth weight and developmental delay among preschool children without disabilities. Am J Epidemiol 1997;146(9):740-9. Zimmer MH, Panko LM. Developmental status and service use among children in the child welfare system. Arch Pediatr Adolesc Med 2006;160(2):183-8. Michael V. Johston, Encephalopathy in Nelson text book of pediatrics 181 E . 2007. Platt, MJ, Cans C, Johnson A, Surman G, Topp M, et al. Trends in cerebral palsy among infants of very low birth weight (<1500 g) or born prematurely (<32 weeks) in 16 European centres: a database study. Lancet 2007; 369(9555):43-50. Robertson CM, Watt MJ, Yasui Y. Changes in the prevalence of cerebral palsy for children born very prematurely within a population-based program over 30 years. JAMA. 2007;297(24):2733-40. Lindsay NM, Healy GN, Colditz PB, Lingwood BE. Use of the Ages and Stages Questionnaire to predict outcome after hypoxic–ischemic encephalopathy in the neonate. J Pediatr Child Health 2008; 44(10):590-5. Yu LM, Hey E, Doyle LW, Farrell B, Spark P, Altman DG et al. Evaluation of the Ages and Stages Questionnaires in identifying children with neurosensory disability in the Magpie Trial follow-up study. Acta Paediatr 2007;96(12):1803-8. 10. Squires J, Bricker D, Potter L. Revision of a parent completed development screening tool: Ages and Stages Questionnaires. J Pediatr Psychol. 1997;22(3):313-28. 11. Glascoe FP. Screening for developmental and behavioral problems. Ment Retard Dev Disabil Res Rev 2005;11(3):173-9. 12. Richter J, Janson H. A validation study of the Norwegian version of the Ages and Stages Questionnaires. Acta Paediatr 2007;96(5):748-52. 13. Shashani S, Vameghi R, Azari N, Sajedi F, Kazemnejad A. Comparing the results of developmental screening of 4-60 months old children in Tehran using ASQ & PDQ. Iran Rehabil J 2011;11(14):3-7. 14. Shashani S, Vameghi R, Azari N, Sajedi F, Kazemnejad A. Validity and reliability determination of Denver developmental screening test- II in 0-6 years old in Tehran. Iran J Pediatr. 2010;20(3):313-22. 15. Jorina E, Andrew M, Elaine M, Faitb G. The Age and Stage Questionnaires: feasibility of use as a screening tool for children in Canada. Can Rural Med. 2008; 13(1):9-14. 16. Gollenberg AI, Lynch CD, Jackson LW, Guinness BM, Msall ME. Concurrent validity of the parent-completed Ages and Stages Questionnaires, 2nd Ed. with the Bayley Scales of Infant Development IIin a low risk sample.Child Care Health Dev 2010;36(4):485-90.